Mapping the evidence on the assessment of fitness to work at heights: a scoping review - Lyndsey Swart; Nicolaas Claassen; Tania Buys (BMJ Open)
Objectives Falls from heights are a leading cause of workplace injuries and fatalities. Ensuring worker fitness is crucial, yet many countries lack formal guidelines for fitness for work (FFW) assessments, posing safety and legal risks. This scoping review sought to identify and map the existing evidence on the assessment of fitness to work at heights.Design Scoping review following the Joanna Briggs Institute Scoping Review Methodology and Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews guidelines.Data sources Searches were conducted in March 2024 across ProQuest Central, Google Scholar, PubMed, Scopus, ScienceDirect, Web of Science and PsycINFO. Grey literature was sourced from the websites of organisations including the International Labour Organisation, Safe Work Australia, Canadian Centre for Occupational Health and Safety, Health and Safety Executive (UK), Occupational Safety and Health Administration (USA), WHO, Centre for Construction Research and Training (USA), Institution of Occupational Safety and Health (UK), South African Society of Occupational Medicine, South African Society of Occupational Health Nursing and Institute for Work at Height (South Africa), in addition to general Google searches.Eligibility criteria for selecting studies Our inclusion criteria encompassed both peer-reviewed and grey literature that addressed either ‘fitness for work at heights’, ‘fitness for work in high-risk settings requiring work at heights’ or human risk factors associated with working at heights.Data extraction and synthesis A data extraction framework and guidance sheet were developed, piloted and refined through team discussions. An iterative review process was followed, with one author extracting and coding data while two authors conducted quality checks. Deductive qualitative content analysis was applied to the extracted data.Results 68 articles met the inclusion criteria, but only 7 directly addressed fitness to work at heights, with the rest focusing on fitness to work in high-risk settings requiring work at heights or human risk factors associated with work at heights. This highlights a lack of peer-reviewed research specific to the topic. Key challenges included FFW assessments failing to reflect job demands, inconsistent application of FFW evaluations, lack of standardisation and inadequate stakeholder collaboration. Legal tensions between employer safety obligations and worker rights were also noted. Critical human risk factors—such as physical and mental limitations, adverse states, human error and rule violations—significantly affected worker safety, though evidence of their specific impact in this context remained limited. Findings on the economic implications of FFW assessments were also inconclusive.Conclusion Assessing FFW at heights is vital for worker safety, yet key challenges persist. This review highlights gaps in evidence on human risk factors and assessment methods. Findings emphasise the need for practice-based research, standardised fitness criteria and interdisciplinary protocols for preplacement assessment and ongoing monitoring.